И.ЮСУПОВТЫҢ «МӘМЕЛЕК ОЙ» ПОЭМАСЫНДА СҮЎРЕТЛЕЎ УСЫЛЫ ҲӘМ ЖАНРЛЫҚ СЫПАТ - Мамбетов, Қ. (FAN va JAMIYAT, 2017)
The article is devoted to the study of genre peculiarities of the poem «The devil’s pit» by I.Yusupov and the analysis of the literary-artictic methods and the structure of the plot in the poem.